Blockade of equilibrative nucleoside transporter 1/2 protects against Pseudomonas aeruginosa–induced acute lung injury and NLRP3 inflammasome activation. Issue 1 (2nd December 2019) - Chambers, Eboni D.; White, Alexis; Vang, Alexander; Wang, Zhengke; Ayala, Alfred; Weng, Tingting; Blackburn, Michael; Choudhary, Gaurav; Rounds, Sharon; Lu, Qing
Abstract: Pseudomonas aeruginosa infections are increasingly multidrug resistant and cause healthcare‐associated pneumonia, a major risk factor for acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). Adenosine is a signaling nucleoside with potential opposing effects; adenosine can either protect against acute lung injury via adenosine receptors or cause lung injury via adenosine receptors or equilibrative nucleoside transporter (ENT)‐dependent intracellular adenosine uptake. We hypothesized that blockade of intracellular adenosine uptake by inhibition of ENT1/2 would increase adenosine receptor signaling and protect against P. aeruginosa– induced acute lung injury. We observed that P. aeruginosa (strain: PA103) infection induced acute lung injury in C57BL/6 mice in a dose‐ and time‐dependent manner. Using ENT1/2 pharmacological inhibitor, nitrobenzylthioinosine (NBTI), and ENT1‐null mice, we demonstrated that ENT blockade elevated lung adenosine levels and significantly attenuated P. aeruginosa– induced acute lung injury, as assessed by lung wet‐to‐dry weight ratio, BAL protein levels, BAL inflammatory cell counts, pro‐inflammatory cytokines, and pulmonary function (total lung volume, static lung compliance, tissue damping, and tissue elastance). Using both agonists and antagonists directed against adenosine receptors A2A R and A2B R, we further demonstrated that ENT1/2 blockade protected against P. aeruginosa – induced acute lung injury via activation of A2A R and A2B R. Additionally, ENT1/2 chemical inhibition and ENT1 knockout prevented P. aeruginosa– induced lung NLRP3 inflammasome activation. Finally, inhibition of inflammasome prevented P. aeruginosa– induced acute lung injury. Our results suggest that targeting ENT1/2 and NLRP3 inflammasome may be novel strategies for prevention and treatment of P. aeruginosa– induced pneumonia and subsequent ARDS.